IMPLEMENTATION OF GOOGLE CLASSROOM IN HISTORY LEARNING TO IMPROVE MOTIVATION AND LEARNING OUTCOMES OF CLASS X STUDENTSAT SMAN 3 MAKASSAR - Arham Arham; Jumadi Jumadi; Najamuddin Najamuddin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research was a quasy experiment which aims to find out the comparison between the use of google classroom media on motivation and learning outcomes in history in the Hindu-Buddhist kingdom of class X students at SMA Negeri 3 Makassar. The research population was all class X students at SMA Negeri 3 Makassar for the academic year 2022/2023 which consisted of 10 classes with a total of 364 students. The selection of the research sample was carried out in a random class manner, so that class X-2 was obtained as the experimental group 1 using google classroom media and class X-8 as the control group without using google classroom media. This research was conducted for 8 hours of lessons (2 meetings for material) and 2 meetings for evaluation. Measuring learning motivation with a questionnaire and learning outcomes was done by giving a multiple-choice test of learning outcomes, included the pretest (students' initial learning outcomes test) and posttest (students' final learning outcomes test). The collected data were analyzed using descriptive statistics and inferentially testing the hypothesis using covariance analysis with a significance level of 0.05. Statistical results of covariance analysis for student motivation (α = 0.05) showed a sig (2-tailed) value of 0.02 <α (0.05) then H0 was rejected and H1 was accepted, while the statistical results of covariance analysis for student learning outcomes (α = 0.05) indicates a sig (2-tailed) value of 0.039 < α = 0.05, then H0 is rejected and H1 was accepted. The assessment of increased motivation and learning outcomes was carried out using N-Gain, where the increase was included in the high category in the experimental class. Based on the results of the study, it can be concluded that there was an application of the Google classroom platform where there was an increase in motivation and learning outcomes in history on Hindu-Buddhist work material for class X students at SMA Negeri 3 Makassar.